Finerenone as a therapeutic option for managing chronic kidney disease (CKD) linked to type 2 diabetes (T2D) and his other potential use. A summary of current research findings - Kubuj, Cezary; Adaśko, Grzegorz; Świda, Michał; Bazarewicz, Jakub; Mazur, Urszula; Siwik, Marcin; Dmowski, Daniel; Michalska, Anna; Ogonowska, Paulina; Waszak, Julia (Quality in Sport, 2025)
Introduction: Chronic kidney disease (CKD) is a common, often late-diagnosed and progressive condition associated with increased morbidity and mortality, mainly due to elevated cardiovascular risk. Diabetes is the one of the leading causes of CKD. Due to the significant role that excessive mineralocorticoid receptor (MR) activation plays in the development of diabetic kidney disease (DKD), new therapies that target this pathway, are being investigated. Finerenone is a non-steroidal selective antagonist that reduces inflammation and fibrosis by blocking MR overactivity in the kidneys, heart, and blood vessels. Materials and Methods: This review is based on a comprehensive analysis of studies on the use of finerenone in patients with CKD and type 2 diabetes (T2D). Additionally, this article explores the potential applications of finerenone. The review was developed using a PubMed database and ClinicalTrials.gov. Results: The results of the FIDELIO-DKD and FIGARO-DKD trials, as well as the FIDELITY pooled analysis, showed that finerenone significantly improved renal and cardiovascular outcomes. They also showed that although hyperkalemia is a major adverse effect of finerenone treatment, the therapy is safe with appropiate monitoring and dose adjustment. In addition, its possible beneficial effects are in non-diabetic CKD, heart failure with preserved (HFpEF) and mildly reduced (HFmrEF) ejection fraction, advanced of CKD with lower estimated glomerular filtration rate (eGFR), and diabetic retinopathy. Conclusion: Clinical studies have confirmed that finerenone is a valuable addition to nephroprotective and cardioprotective strategies in the management of CKD associated with T2D, as reflected in latest clinical guidelines. Its safety profile is generally acceptable. Ongoing clinical trials will help clarify whether the approved indications for finerenone can be extended to non-diabetic CKD or additional clinical settings.